2005
DOI: 10.1515/cclm.2005.002
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein H (apoH)-dependent autoantibodies and apoH protein polymorphism in selected patients showing lupus anticoagulant activity

Abstract: Apolipoprotein H (apoH) is considered to be a necessary cofactor for the binding of certain antiphospholipid antibodies to anionic phospholipids. Some apoH-dependent antiphospholipid antibodies also exert lupus anticoagulant (LA) activity, which seems to depend on antiphospholipid antibody epitope specificity. The aim of this study was to evaluate whether the presence of less frequent apoH alleles may induce structural or conformational changes in these "LA-dependent" regions that may initiate more frequent au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A genome-wide association study has shown that ApoH is a new locus associated with lipoprotein (a) levels [161]. In lupus and primary antiphospholipid syndrome patient samples, ApoH may be a cofactor required for anionic phospholipid binding [162].…”
Section: Apohmentioning
confidence: 99%
“…A genome-wide association study has shown that ApoH is a new locus associated with lipoprotein (a) levels [161]. In lupus and primary antiphospholipid syndrome patient samples, ApoH may be a cofactor required for anionic phospholipid binding [162].…”
Section: Apohmentioning
confidence: 99%